Doping-modulated strain control of bifunctional electrocatalysis for rechargeable zinc–air batteries. Issue 9 (11th August 2021) - Li, Zhao; Wang, Qi; Bai, Xiaowan; Wang, Maoyu; Yang, Zhenzhong; Du, Yingge; Sterbinsky, George E.; Wu, Duojie; Yang, Zhenzhen; Tian, Huajun; Pan, Fuping; Gu, Meng; et al.
Abstract : A new strategy is designed to synthesize strained cobalt fluoride–sulfide catalysts with tunable lattice strains modulated by the Cu-dopant and stabilized local strain by forming a core–shell heterostructure in well-confined porous/tubular films. Abstract : Changes in the local atomic arrangement in a crystal caused by lattice-mismatch-induced strain can efficiently regulate the performance of electrocatalysts for zinc–air batteries (ZABs) in many manners, mainly due to modulated electronic structure configurations that affect the adsorption energies for oxygen-intermediates formed during oxygen reduction and evolution reactions (ORR and OER). However, the application of strain engineering in electrocatalysis has been limited by the strain relaxation caused by structural instability such as dissolution and destruction, leading to insufficient durability towards the ORR/OER. Herein, we propose a doping strategy to modulate the phase transition and formation of self-supported cobalt fluoride–sulfide (CoFS) nanoporous films using a low amount of copper (Cu) as a dopant. This well-defined Cu–CoFS heterostructure overcomes the obstacle of structural instability. Our study of the proposed Cu–CoFS also helps establish the structure–property relationship of strained electrocatalysts by unraveling the role of local strain in regulating the electronic structure of the catalyst. As a proof-of-concept, the Cu–CoFS electrocatalyst with doping-modulated strain exhibited superior onset potentials of 0.91 V and 1.49 V for the ORR and OER, respectively, surpassing commercial Pt/C@RuO2 and benchmarking non-platinum group metal (non-PGM) catalysts. ZABs with the Cu–CoFS catalyst delivered excellent charge/discharge cycling performance with an extremely low voltage gap of 0.5 V at a current density of 10 mA cm −2 and successively 0.93 V at a high current density of 100 mA cm −2 and afforded an outstanding peak power density of 255 mW cm −2 .